Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.
Joint 7th International Symposium on Catalysis in Multiphase Reactors (CAMURE-7)/6th International Symposium on Multifunctional Reactors (ISMR-6), Montreal, CANADA, AUG 23-26, 2009

Isobaric vapor-liquid equilibrium data for binary systems of anisole with methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate at 93.9 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
The present work reports experimental isobaric vapor-liquid equilibrium data at 93.9 kPa pressure using a dynamic recirculation still for four binary pairs of acetates with anisole. The suitability of the experimental data for modeling was established by performing the Herington area test, Van Ness test, and mean absolute deviation test. Binary interaction parameters necessary for process modeling were derived through the regression of the VLE data for Wilson, NRTL, and UNIQUAC activity coefficient models with a suitable objective function. VLE data in the form of T-x, y plots indicates no formation of azeotropes for all pairs.

Intensified reactive distillation configurations for production of dimethyl ether - Gor, Nikhil K.; Mali, Nilesh A.; Joshi, Sunil S. (Chemical Engineering and Processing-Process Intensification, 2020)
The combustion properties of dimethyl ether (DME) are similar to the conventional fuels; hence it is being used as a promising green energy source. The conventional method of DME production by methanol dehydration is highly energy consuming due to the use of a series of distillation columns. In the present study, an energy efficient reactive distillation configuration is proposed for DME production which leads to higher methanol conversion with less energy requirement as compared to reported configurations. The reactive distillation (RD) and dual reaction zone reactive divided wall column (RDWC) were analyzed using steady state ASPEN simulations. Subsequently, all the design parameters were optimized by sensitivity analysis to minimize the Total Annual Cost (TAC) of the configuration. The results showed that the RD column is more energy efficient than RDWC as it requires 10.68 % less TAC. The proposed RD and dual reaction zone RDWC configurations were found to have less specific energy requirements and less cost per kg of DME than any other configuration reported earlier.
Keywords: Energy efficient configuration; Reactive distillation; Reactive divided wall column; Total annual cost